Stimulasi Pertumbuhan Bibit Kopi Arabika (Coffea Arabika L) dengan Penambahan Ekstrak Rumput Laut (Eucheuma Cottonii Weber-Van Bosse) dan Kotoran Kelinci - Dewi, Putri Lestari; Warsito, Kabul; Setiawan, Andi Setiawan (Riwayat: Educational Journal of History and Humanities, 2025)
This study was conducted to evaluate the effects of biostimulant applications derived from seaweed extract (Eucheuma cottonii Weber-van Bosse) and fertilizer based on rabbit manure on the growth and development of Arabica coffee seedlings (Coffea arabica L.). The research is motivated by the critical need for high-quality seedling production to support successful coffee cultivation, and by the potential use of seaweed and rabbit manure as sources of organic nutrients and natural biostimulants. The experiment was carried out in a greenhouse at Universitas Pembangunan Panca Budi, Medan, using a factorial Randomized Block Design (RBD) with two treatment variables: seaweed extract concentrations (0 ml/L, 5 ml/L, 10 ml/L, and 15 ml/L) and rabbit manure compositions (0%, 20%, 30%, and 40% of the total growth media). A total of 16 treatment combinations were tested, each replicated three times. Parameters observed included plant height, leaf number, leaf area, root length, and total plant biomass. This study aims to contribute scientific insights into the effectiveness of treatment combinations in promoting optimal and sustainable early growth of coffee plants.